Comparing Anxiety, Depression, and Stress in Consanguineous Versus Non-Consanguineous Parents of Children With Deafness in Baqiyatallah Hospital's Cochlear Implant Center From 2007 to 2009 - Sima Noohi; Mohammad Ghalamfarsa; Esmat Davoudi Monfared (Baqiyatallah University of Medical Sciences, 2018)
Background: The birth of a child with a hearing disability is a stressful event in the family. Since consanguineous marriages are associated with the incidence of congenital hearing loss, it is expected that such parents will experience greater psychological problems. Objective: The current study investigated and compared anxiety, depression, and stress in parents of children with severe hearing loss who have undergone cochlear implantation with a focus on the relation between parents (consanguineous vs. non-consanguineous). Methods: This cross-sectional study was conducted on all 180 couples (360 individuals) who had become parents and attended Baqiyatallah hospital's Cochlear Implant Center from 2007 to 2009. The participants included two groups of consanguineous (125 couples) and non-consanguineous (55 couples) parents. After providing consent to participate in this study, the participants completed the short form of the Depression and Anxiety and Stress Scale questionnaire (DASS-21). Data analysis was done using SPSS 17 and t test. Results: The participating parents had high levels of depression, anxiety, and stress. Depression and anxiety were significantly higher among the consanguineous parents (P=0.001 and P=0.005, respectively). However, stress levels were not significantly different between the 2 groups. Moreover, compared to the fathers, the mothers had higher levels of depression, anxiety, and stress (P<0.05). Conclusion: Based on these findings, it may be concluded that the birth of a child with hearing loss can be the source of psychological problems in parents, particularly in consanguineous parents. Furthermore, mothers are more psychologically vulnerable than fathers.